Multijunction photovoltaic devices with metal oxynitride layers - Patents.com
By introducing silicon nitride nanoparticles on the graphene surface to form graphene/Si3N4 composite materials, the problem of the decrease in efficiency of polycrystalline silicon/graphene batteries at high temperatures is solved, and higher high-temperature stability and electrochemical performance are achieved.
Patent Information
- Application Number
- JP2022577467
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-18
- Filing Date
- 2021-06-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-06-17
AI Technical Summary
The existing polysilicon/graphene batteries have a problem of reduced efficiency at high temperatures, and traditional graphene materials have poor stability at high temperatures, which affects the long life of the battery.
Modified graphene material is used to form graphene/Si3N4 composite materials by introducing silicon nitride (Si3N4) nanoparticles on the graphene surface to improve the high temperature stability and electrochemical performance of the material.
The modified graphene/Si3N4 composite material exhibits higher battery efficiency and better stability at high temperatures, extending the service life of the battery and solving the problem of the reduction in efficiency of traditional graphene materials at high temperatures.
Smart Images

Figure 0007662130000002 
Figure 0007662130000003 
Figure 0007662130000004
Abstract
Description
[Technical field]
[0001] The present invention relates to photovoltaic (PV) devices, and in particular to multi-junction photovoltaic devices, such as tandem solar cells and PV panels, and methods for their manufacture. [Background technology]
[0002] Solar energy conversion is one of the most promising technologies for providing renewable energy. However, reducing the costs of producing devices that effectively capture solar energy, especially the costs of materials and the necessary equipment, remains critical to facilitating their widespread adoption.
[0003] Single-junction solar cells, such as those made from silicon pn junctions, have a maximum theoretical efficiency of about 29% and a practical efficiency of up to 26% under AM1.5G conditions (see, for example, the book “Photovoltaic Solar Energy ― from Fundamentals to Applications” edited by A Reinders et al., Wiley ISBN9781118927465
[2017] , p.164). However, when a cell made of a material with a higher bandgap is stacked on top of a silicon single-junction cell (or other types of single-junction cell) and connected in series, the limiting theoretical efficiency increases to more than 40%. Therefore, tandem and other multi-junction cell technologies are currently being greeted with increasing interest.
[0004] A particularly promising class of monolithic tandem or multijunction photovoltaic device solar cells combine a subcell comprising a perovskite (such as an organometal halide perovskite) with a second subcell that may comprise, for example, a photoactive silicon absorber. Perovskites are known in the art to be ideal light absorbers in PV devices because they exhibit favorable bandgaps, high absorption coefficients, and long diffusion lengths.
[0005] Conventional perovskite / silicon tandem solar cells incorporate a transparent conductive oxide (TCO) layer (on top of the silicon bottom subcell) required to form a low ohmic tunneling recombination contact between the silicon subcell and the perovskite subcell. Typical examples of TCO materials include, for example, indium tin oxide (ITO) or aluminum, gallium or indium doped zinc oxide (AZO, GZO or IZO), of which ITO is the most commonly used.
[0006] However, the use of interconnect layers with ITO can be disadvantageous for several reasons. First, ITO layers tend to form highly reflective interfaces due to unfavorable ordering of refractive indices. Furthermore, they exhibit high lateral conductivity, which can lead to the existence of shunt paths through the perovskite absorber in the finished device.
[0007] To reduce reflection between the perovskite top cell and the silicon bottom cell, a substoichiometric amount of nanocrystalline silicon oxide (nc-SiO ) was placed below the ITO layer, which forms the contact to the p-layer of the top cell, and above the amorphous silicon i-layer. x The use of a .sup.2N-type .sup.3 ...
[0008] WO 2018 / 150203 further discloses that the incorporation of an intermediate region between the perovskite-based subcell and the photoactive silicon-based subcell with an interconnect layer made of a dual-phase material with elongated silicon nanocrystals embedded in a silicon oxide matrix can mitigate the adverse effects of local shunt paths and can be tailored to reduce reflection losses.
[0009] However, the process used in WO 2018 / 150203 for the deposition of dual-phase materials is a specialized plasma enhanced chemical vapor deposition (PECVD), which relies on the interplay of several surface chemical mechanisms, such as selective etching, large surface diffusion, and chemical annealing, to achieve structures with the desired lateral and vertical conductivity, all of which therefore lead to a low deposition rate of approximately 0.2 nm / s. In addition, the relatively high chamber pressure combined with the high gas dissociation rate in this particular regime can lead to plasma polymerization during the process, which adversely affects the stability and reproducibility of the process. Overall, the PECVD process also requires expensive and complex equipment.
[0010] In view of the above, it remains desirable to provide multi-junction photovoltaic devices that overcome the above-mentioned shortcomings of known interconnect layers and that can be simultaneously produced in a simpler, faster, more consistent and less expensive manner. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] International Publication No. 2018 / 150203 Brochure [Non-patent literature]
[0012] [Non-Patent Document 1] A Reinders et al., “Photovoltaic Solar Energy ― from Fundamentals to Applications”, Wiley ISBN9781118927465
[2017] , p.164 [Non-Patent Document 2] L. Mazzarella et al., Advanced Energy Materials 2019, 9(14), 1803241 Summary of the Invention
[0013] The present invention alleviates these drawbacks by using the subject matter of the claims defined herein. Further advantages of the present invention will be explained in detail in the following sections.
[0014] According to a first aspect, the present invention relates to a multi-junction photovoltaic device having a first subcell and a second subcell, the first subcell having a layer with a perovskite light absorber material and a metal oxynitride (M oxynitride) between the first and second subcell. n O x N y In contrast to nanocrystalline silicon oxide, metal oxynitrides, such as titanium oxynitride, can be deposited by physical vapor deposition (e.g., sputtering) at higher deposition rates and the refractive index of the resulting layer can be easily adjusted to a desired refractive index that allows for reduced reflection losses, which substantially improves the layer absorbance of the bottom subcell. At the same time, the metal (e.g., titanium) oxynitride layer is transparent to infrared light and exhibits excellent electrical conductivity properties for efficient electrical interconnection of the two subcells.
[0015] A second aspect of the invention relates to a method of manufacturing a multi-junction photovoltaic device having a first subcell having a layer comprising a perovskite light absorber material and a second subcell, the method comprising depositing a metal oxynitride layer between the first and second subcells.
[0016] Preferred embodiments of multi-junction photovoltaic devices according to the present invention, methods for their manufacture, and other aspects of the invention are set forth in the following description and claims. [Brief description of the drawings]
[0017] Embodiments of the invention will now be described, by way of example only, with reference to the accompanying schematic drawings in which: [Figure 1]1 illustrates a schematic diagram of an example of a monolithically integrated multi-junction photovoltaic device according to the present invention. [Diagram 2] 1 shows an embodiment of a monolithically integrated multijunction photovoltaic device according to the present invention having an inverted structure. [Diagram 3] 2 shows another embodiment of a monolithically integrated multijunction photovoltaic device according to the present invention having a general structure. [Figure 4] Power conversion efficiency (PCE), short circuit current density (JSC), open circuit voltage (VOC), and fill factor (FF) for six tandem cells, three with no interlayer and three with TiOxNy interlayer, are shown. Results are normalized to the average value for the no interlayer split for each of the four parameters listed above. [Diagram 5] The external quantum efficiency (EQE) measured from two representative tandem cells, one from a split without an interlayer and the other from a split with a TiOxNy interlayer, is shown versus wavelength (in nm). The perovskite top cell absorbs in the 300-780 nm range, and the silicon bottom cell absorbs from 500-1200 nm. [Figure 6] Figure 6 shows box plots of the JSC of the perovskite sub-cell and the silicon sub-cell calculated from the EQE curves in Figure 5 for no interlayer and for a TiOxNy interlayer. [Figure 7] An example of a multijunction photovoltaic device cell stack with no interlayer split (left) and with a TiOxNy interlayer split (right) is shown. [Figure 8] The current density JSC-voltage characteristics of split 1 (top), which is a split without an intermediate layer, and split 2 (bottom), which is a split with a TiOxNy intermediate layer, are shown. [Figure 9] FIG. 1 shows a graph of refractive index (including absorption or extinction coefficient “nk”) versus wavelength measured by spectroscopic ellipsometry to illustrate the optical properties of a series of TiOxNy films deposited at gas flow rates of 0 sccm (standard cubic centimeters), 40 sccm, and 80 sccm. [Figure 10]Optical simulation results for the no interlayer split (top) and the TiOxNy interlayer split (bottom) are shown, with the absorbance for the simulated EQE for each layer in the simulated stack displayed. The legend to the right of the spectrum corresponds to the tandem cell stack and its respective components. [Figure 11] Figure 1 shows simulated bottom subcell Jsc values for various TiOxNy interlayers, nc-Si reference (baseline), and nc-SiOx reference. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] For a more complete understanding of the present invention, reference is now made to the following description of illustrative embodiments thereof.
[0019] Multijunction Photovoltaic Devices In a first embodiment, the present invention relates to a multijunction photovoltaic device comprising a first subcell and a second subcell, characterized in that the first subcell comprises a layer comprising a perovskite light absorber material and a metal (e.g. titanium) oxynitride layer is provided between the first and second subcell. "Multijunction" means two or more. Preferably, the second subcell is a silicon subcell. Advantageously, the photovoltaic device has a monolithically integrated structure, e.g. a tandem structure, comprising the first and second subcells. In a monolithically integrated multijunction photovoltaic device, two or more photovoltaic subcells are placed directly on top of each other and are therefore electrically connected in series. The photovoltaic device may optionally further comprise intermediate regions connecting the first subcell to the second subcell, each intermediate region comprising one or more conductive interconnect layers.
[0020] An exemplary schematic structure of a photovoltaic device according to the invention is shown in Figure 1. The illustrated monolithic multijunction photovoltaic device (100) comprises a top perovskite-based subcell as a first subcell (110) and a bottom second subcell (120) between a front electrode (101) and a back electrode (102), with a metal (e.g. titanium) oxynitride layer (103) between the first subcell (110) and the second subcell (120). This layer is represented in this figure by the formula MO x N y It is expressed as M n O x N y It will be appreciated that additional layers may be provided between the first and second subcells.
[0021] The term "front electrode" as used herein refers to an electrode provided on the side or surface of a photovoltaic device that is intended to be exposed to sunlight. Thus, the front electrode typically needs to be transparent or semi-transparent to allow light to pass through it to the photoactive layer provided below the front electrode. Thus, the term "back electrode" as used herein refers to an electrode provided on the side or surface of a photovoltaic device opposite the side or surface that is intended to be exposed to sunlight. The selection of the front and back electrodes of the optoelectronic device of the present invention can be suitably selected by the skilled artisan from materials known in the art and may depend on the structure type. Representative materials include, but are not limited to, metals and metal oxides, such as tin oxide ITO (indium tin oxide), FTO (fluorine doped tin oxide), or AZO (aluminum doped tin oxide), and high work function metals, such as aluminum, gold, silver, nickel, palladium, or platinum. The thickness of the front and back electrodes can be suitably selected by one skilled in the art and may typically be in the range of 50 nm to 600 nm, more typically in the range of 300 nm to 500 nm. For example, the thickness may be 400 nm. The first electrode is often disposed on a glass substrate.
[0022] The term "perovskite" as used herein refers to a material with a structure related to that of CaTiO3. The structure of CaTiO3 can be represented by the formula ABX3, where A and B represent cations of different sizes and X is an anion. Within the unit cell, the A cations are at (0,0,0), the B cations are at (1 / 2,1 / 2,1 / 2), and the X anions are at (1 / 2,1 / 2,0). The A cations are usually larger than the B cations. As will be appreciated by those skilled in the art, A, B, and X can be varied to distort the structure of the perovskite material from that adopted by CaTiO3 to a distorted structure of lower symmetry. Symmetry is also lower when the material has a layer with a structure related to that of CaTiO3. As those skilled in the art will appreciate, perovskite materials can be represented by the formula [A][B][X]3, where [A] is at least one cation, [B] is at least one cation, and [X] is at least one anion. When a perovskite has two or more A cations, different A cations can be distributed regularly or irregularly on the A site. When a perovskite has two or more B cations, different B cations can be distributed regularly or irregularly on the B site. When a perovskite has two or more X anions, different X anions can be distributed regularly or irregularly on the X site. The symmetry of perovskites with two or more A cations, two or more B cations, or two or more X anions is often lower than that of CaTiO3.
[0023] In general, the term "perovskite" as used herein refers to (a) a material with a three-dimensional crystal structure related to that of CaTiO3, or (b) a material having layers of material with a structure related to that of CaTiO3. Although both of these categories of perovskites may be used in devices according to the invention, it may be preferable to use perovskites of the first category (a), i.e., perovskites with a three-dimensional (3D) crystal structure. Such perovskites typically have a 3D network of perovskite unit cells with no separation between the layers. On the other hand, perovskites of the second category (b) include perovskites with a two-dimensional (2D) layered structure. Perovskites with a 2D layered structure may have layers of perovskite unit cells separated by (intercalated) molecules, an example of such a 2D layered perovskite is [2-(1-cyclohexenyl)ethylammonium]2PbBr4. 2D layered perovskites tend to have high exciton binding energies, which favor the generation of bound electron / hole pairs (excitons) under photoexcitation rather than free charge carriers. The bound electron / hole pairs may not be mobile enough to reach a p-type or n-type contact, where they can transfer (ionize) to generate free charges. Thus, to generate free charges, the exciton binding energy must be overcome, which represents an energy cost to the charge generation process, resulting in lower voltages and lower efficiencies in solar cells. In contrast, perovskites with 3D crystal structures tend to have much lower exciton binding energies (on the order of thermal energy), and thus can generate free carriers directly following photoexcitation. Thus, the perovskite semiconductors used in the devices and processes of the present invention are preferably perovskites with three-dimensional crystal structures.
[0024] In a preferred embodiment, the perovskite material is of the general formula [A][B][X]3, where [A] is one or more monovalent cations, [B] is one or more divalent inorganic cations, and [X] is one or more halide anions, preferably selected from fluoride, chloride, bromide, and iodide, and more preferably selected from chloride, bromide, and iodide. More preferably, [X] comprises one or more halide anions selected from bromide and iodide. [A] is preferably methylammonium (CH3NH3 + ), formamidinium (HC(NH)2)2 + ), and ethylammonium (CH3CH2NH3 + ), preferably methylammonium (CH3NH3 + ) and formamidinium (HC(NH)2)2 + ) is an organic cation selected from the group consisting of Cs + , Rb + , Cu + , Pd + , Pt + , Ag + , Au + , Rh + , and Ru + [B] preferably has one or more inorganic cations selected from Pb 2+ and Sn 2+ At least one divalent inorganic cation selected from the group consisting of Pb 2+ Further examples of suitable perovskite materials are disclosed, for example, in Kojima, A et al., Journal of the American Chemical Society 2009, 131(17), pp. 6050-1, Zuo, C et al., Adv. Sci. 2016, 3, 1500324, WO 2013 / 171517, WO 2014 / 045021, WO 2016 / 198898, and WO 2018 / 150203.
[0025] The term "perovskite light absorber material" as used herein refers to a perovskite material that is capable of absorbing light and thereby generating free charge carriers. However, the perovskite material may also be a perovskite material that may be capable of emitting light by accepting both electron and hole charges that subsequently recombine to emit light.
[0026] As will be appreciated by those skilled in the art, the perovskite material used in the present invention may be a perovskite that acts as an n-type electron transport semiconductor when photodoped. Alternatively, the perovskite material used in the present invention may be a perovskite that acts as a p-type hole transport semiconductor when photodoped. Thus, the perovskite may be n-type, p-type, or may be an intrinsic semiconductor. In a preferred embodiment, the perovskite used is one that acts as an n-type electron transport semiconductor when photodoped. Perovskite materials can exhibit ambipolar charge transport and therefore can function as both n-type and p-type semiconductors. In particular, perovskites can function as both n-type and p-type semiconductors depending on the type of junction formed between the perovskite and the adjacent material. Typically, the perovskite semiconductor used in the present invention is a photosensitizing material, i.e. a material that can perform both photogeneration and charge transport.
[0027] As used herein, the term “metal oxynitride” refers to a compound of the formula M n O x N y The metal oxynitride layer may be suitably adjusted to balance the desired electrical conductivity with the optical transmittance and reflectance of the metal oxynitride layer by suitably adjusting x and y, as well as the concentration ratio x / y (expressed as the ratio of the concentration of oxygen x to the concentration of nitrogen y in atomic percent, also referred to as the O / N ratio), depending on the deposition thickness of the layer. The metal M is preferably an early transition metal, e.g., a metal from groups 4 to 6 of the periodic table. The early transition metal oxynitrides (M n O x N y) are known to form non-stoichiometric interstitial compounds with large free carrier concentrations. The formula of the metal oxynitride is preferably M, where n is 1 or 2. n O x N y The advantages of metal nitrides over their oxide counterparts include simple fabrication methods (they can all be deposited by sputtering) and the incorporation of N allows for optimization of the refractive index (RI). These aspects make these materials highly desirable for interlayer applications in multijunction photovoltaic devices. Systems that can allow fine tuning would be advantageous to achieve the highest efficiencies.
[0028] Suitable metals for the metal oxynitrides are Ti, W, Mo, Hf, Ta, Nb, Zr, Cr, and V, which form the following oxynitrides: Ti n O x N y , W n O x N y , Mo n O x N y , Hf n O x N y , Ta n O x N y , Nb n O x N y , Zr n O x N y , Cr n O x N y , V n O x N y The RI of the corresponding metal oxides for these oxynitrides is given in the table below, and the use of N can further fine-tune the RI to be suitable for use in the present invention. The oxides given in this table are merely exemplary, and the present invention is not limited thereto. [Table 1]
[0029] The range for metal oxides shown in the table above is approximately 1.8-2.5, which can be further adjusted with nitrogen content to suit the present invention, with the preferred refractive index for metal oxynitrides being between 2.39-2.9.
[0030] The most preferred metal is titanium. The term "titanium oxynitride" as used herein has the formula TiO x N y The x and y, as well as the concentration ratio x / y (expressed as the ratio of the concentration x of oxygen to the concentration y of nitrogen in atomic percent, also referred to as the O / N ratio), may be suitably adjusted according to the deposition thickness of the layer to balance the desired electrical conductivity and the optical transmittance and reflectance of the titanium oxynitride layer. In this respect, it is preferred that x is in the range of 0.60 to 0.95 and y is in the range of 0.10 to 1.2. Additionally or alternatively, a ratio x / y in the range of 0.4 to 5 is preferred, with a ratio x / y in the range of 0.6 to 4.5 being particularly preferred. As will be explained below in relation to the second embodiment, TiO x N y The O / N ratio and properties of the film can be controlled in a straightforward manner by suitably adjusting the deposition conditions. As mentioned above, the deposition of the titanium oxynitride layer can be performed by physical vapor deposition (PVD) methods (such as sputtering), thus requiring less complex equipment and allowing a higher deposition rate compared to the PECVD methods used in the preparation of known interconnect layers.
[0031] In general, it is preferred to adapt the layer of metal (e.g. titanium) oxynitride to have a refractive index n between the refractive index of the perovskite material layer and the refractive index of the material on which the second subcell is based. Also, if additional intermediate layers are used between the first and second subcells, it is preferred to adapt the refractive index of each layer increasing in the direction of the light path in order to minimize reflection losses. In a preferred embodiment, the layer of titanium oxynitride is adapted to have a refractive index in the range of 2.3 to 3.7, more preferably in the range of 2.3 to 3.2, particularly preferably between 2.3 and 2.9, e.g. 2.4 to 2.8, the values given being typically measured for light having a wavelength of 600 nm. In a preferred embodiment, the layer of titanium oxynitride has a thickness between 15 nm and 300 nm, more preferably between 20 nm and 200 nm, and particularly preferably between 40 nm and 160 nm. By adjusting the optical thickness and refractive index of the titanium oxynitride layer according to the above ranges, the reflectivity can be effectively reduced.
[0032] In a preferred embodiment of the invention, the first subcell also comprises an n-type semiconductor layer on one surface of the layer comprising perovskite absorber material, and a p-type semiconductor layer on the other surface of the layer comprising perovskite absorber material (i.e. the surface opposite to the n-type semiconductor layer).
[0033] The term "n-type" as used herein refers to a region, layer, or material having an extrinsic semiconductor with a higher concentration of electrons than holes. Similarly, the term "n-type semiconductor layer" refers to a layer of an electron-transporting (i.e., n-type) semiconducting material. The material can be a single electron-transporting semiconductor compound or elemental material, or a mixture of two or more electron-transporting semiconductor compounds or elemental materials. The electron-transporting semiconductor compounds or elemental materials can be undoped or doped with one or more dopant elements. Examples of n-type semiconducting materials include, but are not limited to, inorganic materials selected from oxides of titanium, tin, zinc, niobium, tantalum, tungsten, indium, gallium, neodymium, palladium, cadmium, or oxides of a mixture of two or more of these metals; sulfides of cadmium, tin, copper, zinc, or sulfides of a mixture of two or more of these metals; selenides of cadmium, zinc, indium, gallium, or selenides of a mixture of two or more of these metals; or tellurides of cadmium, zinc, cadmium, tin, or tellurides of a mixture of two or more of these metals. Further examples include organic and polymeric electron transport materials and electrolytes, such as, for example, organic electron transport materials having fullerene or fullerene derivatives, perylene or its derivatives, or poly{[N,N0-bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximido)-2,6-diyl]-alt-5,50-(2,20-bithiophene)} (P(NDI2OD-T2)).
[0034] The term "p-type" as used herein refers to a region, layer, or material having an extrinsic semiconductor with a higher concentration of holes than electrons. The term "p-type semiconductor layer" refers to a layer of a hole-transporting (i.e., p-type) semiconducting material. The hole-transporting (i.e., p-type) semiconducting material may be a single hole-transporting semiconducting compound or elemental material, or a mixture of two or more hole-transporting semiconducting compounds or elemental materials. The hole-transporting semiconducting compounds or elemental materials may be undoped or doped with one or more dopant elements. The p-type layers used in the optoelectronic devices of the present invention may comprise inorganic or organic p-type materials. Examples of p-type semiconducting materials include, but are not limited to, polymeric or molecular hole transporters (e.g., spiro-OMeTAD (2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)9,9'-spirobifluorene)), P3HT (poly(3-hexylthiophene)), PCPDTBT (poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-diyl]]), PVK (poly(N-vinylcarbazole)), HTM-TFSI (1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide), Li-TFSI (lithium bis(trifluoromethanesulfonyl)imide) or tBP (tert-butylpyridine), molecular hole transporters. transport compounds, polymeric hole transport compounds and copolymer hole transport compounds (e.g., polymers or copolymers having one or more of thiophenyl, phenelenyl, dithiazolyl, benzothiazolyl, diketopyrrolopyrrolyl, ethoxydithiophenyl, amino, triphenylamino, carbozolyl, ethylenedioxythiophenyl, dioxythiophenyl, or fluorenyl), m-MTDATA (4,4',4"-tris(methylphenylphenylamino)triphenylamine), MeOTPD (N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine), BP2T (5,5'-di(biphenyl-4-yl)-2,2'-bithiophene), Di-NPB (N,N'-di-[(1-naphthyl)-N,N'-diphenyl]-1,1'-biphenyl)-4,4'-diamine), α-NPB (N,N'-Di(naphthalen-1-yl)-N,N'-diphenyl-benzidine), TNATA (4,4',4"-tris-(N-(naphthlen-2-yl)-N-phenylamine)triphenylamine), BPAPF (9,9-bis[4-(N,N-bis-biphenyl-4-yl-amino)phenyl]-9H-fluorene), spiro-NPB (N2,N7-Di-1-naphthalenyl-N2,N7-diphenyl-9,9'-spirobi[9H-fluorene]-2,7-diamine), 4P-TPD (4,4'-bis-(N,N-diphenylamino)-tetraphenyl), PEDO T:PSS, spiro-OMeTAD, inorganic hole transport compounds (e.g., oxides of nickel, vanadium, copper or molybdenum, CuI, CuBr, CuSCN, CuO, CuO or CIS, perovskites, amorphous Si, p-type Group IV semiconductors, p-type Group III-V semiconductors, p-type Group II-VI semiconductors, p-type Group I-VII semiconductors, p-type Group IV-VI semiconductors, p-type Group V-VI semiconductors, and p-type Group II-V semiconductors). Both inorganic and organic p-type semiconducting materials may be undoped or doped with dopants known in the art.
[0035] The first photovoltaic subcell may have a conventional structure, with the first subcell having a perovskite absorber material arranged such that the n-type region is adjacent to the second subcell, and the photovoltaic device is preferably configured to be illuminated through the p-type region of the first subcell.
[0036] Alternatively, the first photovoltaic subcell may have an inverted structure, with the first subcell having the perovskite absorber material arranged with the p-type region adjacent to the second subcell, and the photovoltaic device is preferably configured to be illuminated through the n-type region of the first subcell.
[0037] In such a configuration, it may further be preferred for the layer of metal (e.g. titanium) oxynitride to be adjacent to and in contact with the semiconductor layer closer to the second subcell, i.e., the p-type semiconductor layer if the multijunction device configuration is normal, or the n-type semiconductor layer if the multijunction device configuration is inverted.
[0038] In another preferred configuration, one of the n-type or p-type semiconductor layers of the first subcell is adjacent to and in contact with a major surface of the light-transmitting conductive oxide layer, and the opposite major surface of the light-transmitting conductive oxide layer is adjacent to and in contact with the titanium oxynitride layer. In such a configuration, the light-transmitting conductive oxide layer may advantageously serve to protect the titanium oxynitride layer during deposition of the first subcell. The material used for the light-transmitting conductive oxide layer may be selected from transparent and semi-transparent conductive oxides (TCOs) known in the art. Typically, transparent materials have an average transmittance of about 100% or 90 to 100% to light, and semi-transparent materials typically have an average transmittance of 10 to 90%, typically 40 to 60%, to light. Examples of these may include ITO (indium tin oxide), FTO (fluorine doped tin oxide), or AZO (aluminum doped tin oxide). The light-transmitting conductive oxide layer preferably has a thickness of 1 nm to 25 nm, preferably 5 nm to 22 nm, more preferably 10 nm to 20 nm. It is noted, however, that the light-transmitting conductive oxide layer is not essential and may be omitted, which may further simplify the manufacturing method and reduce costs. In this context, it may be preferred that no transparent conductive oxide layer is provided in addition to the metal (e.g. titanium) oxynitride layer between the first subcell and the second subcell layer.
[0039] In a preferred embodiment, the second subcell is a silicon subcell. It preferably comprises a layer of crystalline silicon absorber material. More preferably, the second subcell comprises a silicon heterojunction (SHJ). Alternatively, the second subcell may comprise other forms of silicon-based subcell (including, for example, a diffused silicon junction).
[0040] The term "silicon heterojunction" refers to an amorphous silicon / crystalline silicon heterojunction that uses a crystalline silicon (c-Si) wafer as the photoactive absorber and an amorphous silicon (a-Si) thin film for junction formation and surface passivation. Thus, in a preferred embodiment, the second subcell has a layer of crystalline silicon sandwiched between two layers of undoped amorphous silicon.
[0041] When a thin layer of intrinsic amorphous silicon (a-Si) is present as a passivation / buffer layer, the silicon heterojunction (SHJ) is sometimes referred to as a heterojunction with intrinsic thin layer (HIT). Thus, a silicon heterojunction (SHJ) typically has a p-type a-Si emitter, an intrinsic a-Si passivation / buffer layer, an n-type c-Si photoactive absorber, another intrinsic a-Si passivation / buffer layer, and a back- or front-surface field (BSF or FSF) layer of n-type a-Si. Optionally, the silicon heterojunction (SHJ) can further have a layer of transparent conductive oxide (TCO) (e.g., ITO) between the back-surface field (BSF) layer and the back electrode, which can help maximize the infrared response by increasing the internal reflectance at the back surface. The SHJ cell can be illuminated through either the p-side or the n-side. In the latter case, it may be called a back-junction solar cell. Thus, an SHJ cell can be combined with a normal or inverted perovskite cell to form a tandem cell.
[0042] In a preferred embodiment, an interconnect layer having doped nanocrystalline silicon (ie, an nc-Si:H layer) may be provided between a layer of undoped amorphous silicon and a layer of metal (eg, titanium) oxynitride.
[0043] One preferred construction of a multi-junction photovoltaic device according to the present invention comprises, in the following order: a) Front electrode, b) a first subcell having a layer with a perovskite light absorber, the first subcell having an n-type semiconductor layer on one surface of the layer with the perovskite light absorber and a p-type semiconductor layer on the other surface of the layer with the perovskite light absorber; c) an optional light-transmissive conductive oxide layer; d) metal oxynitride layer, e) a doped amorphous silicon layer; f) a second subcell having a layer of crystalline silicon absorber material between the first and second undoped amorphous silicon layers; and g) Back electrode, has.
[0044] An example of a suitable device configuration using such a silicon heterojunction in the second subcell (ie, the bottom cell) is shown in FIGS.
[0045] FIG. 2 shows a schematic diagram of a monolithically integrated multijunction photovoltaic device 200 having a first / top subcell 210 with a photoactive region with a perovskite material, and a second / bottom subcell 220 with a photoactive silicon absorber. The multijunction photovoltaic device 200 has a monolithically integrated structure and thus has only two electrodes, a front electrode 201 and a back electrode 202, between which the first subcell 210 and the second subcell 220 are disposed. In particular, the first subcell 210 contacts the front electrode 201, and the second subcell 220 contacts the back electrode 202. The monolithically integrated multijunction photovoltaic device may also typically have a metal grid (not shown) as a top contact on the top surface of the front electrode 201. For example, a metal grid or fingers made by screen printing of silver and / or copper paste may be provided on the top contact. In the example of FIG. 2, the first subcell 210 has an inverted structure. Specifically, the first subcell 210 is arranged such that the p-type semiconductor layer 213 is adjacent to the second subcell 220. The photovoltaic device 200 is then configured to be illuminated through the n-type semiconductor layer 212 of the first subcell 210. The photoactive region formed by the perovskite layer 211 is located between the p-type semiconductor layer 213 and the n-type semiconductor layer 212. The second subcell (bottom cell) 220 of FIG. 2 has a silicon heterojunction (SHJ) with a crystalline silicon layer 221, in this case an n-type c-Si photoactive absorber, sandwiched between a first undoped amorphous silicon layer 222 and a second undoped amorphous silicon layer 224, which act as an intrinsic a-Si (i.e., a-Si(i)) passivation / buffer layer. A p-type amorphous silicon (a-Si) layer 225 is formed beneath the second undoped amorphous silicon layer 224 and adjacent to the back electrode 202. A titanium oxynitride layer 203 is essentially provided between the first subcell 210 and the second subcell 220.As further shown in the preferred embodiment of FIG. 2, a doped (i.e., n-doped) amorphous silicon layer 205 is provided between the second subcell 220 and the titanium oxynitride layer 203, which serves to prevent sputter damage to the first undoped amorphous silicon layer 222 (i.e., the a-Si(i) layer) and provides a good electron-selective contact to the second subcell 220. Additionally, the structure of FIG. 2 includes a light-transmitting conductive oxide (TCO) layer 204, which may be made of ITO or the like, between the p-type region of the first subcell 210 and the titanium oxynitride layer 203. The TCO layer 204 may protect the stack from oxidation prior to deposition of the n-type region of the first subcell 210. However, it is understood that the presence of the light-transmitting conductive oxide layer 204 and the doped amorphous silicon layer 205 are optional.
[0046] As mentioned above, multijunction devices according to the present invention may include both normal and inverted configurations. An example of a normal structure is shown in FIG. 3. The multijunction photovoltaic device 300 shown therein has a front electrode 301 and a back electrode 302, with a first subcell 310 and a second subcell 320 disposed between these two electrodes. In particular, the first subcell 310 contacts the front electrode 301, and the second subcell 320 contacts the back electrode 302. The first subcell 310 is disposed such that the n-type semiconductor layer 312 is adjacent to the second subcell 320. The photovoltaic device 300 is then configured to be illuminated through the p-type semiconductor layer 313 of the first subcell 310. The photoactive region formed by the perovskite layer 311 is disposed between the p-type semiconductor layer 313 and the n-type semiconductor layer 312. The second subcell (bottom cell) 320 of FIG. 3 has a silicon heterojunction (SHJ) with a crystalline silicon layer 321 sandwiched between a first undoped amorphous silicon layer 322 and a second undoped amorphous silicon layer 324, which act as passivation / buffer layers. An n-type amorphous silicon (a-Si) layer 325 is formed adjacent to the back electrode 302 beneath the second undoped amorphous silicon layer 324. Additionally, a doped (i.e., p-doped) amorphous silicon layer 305 is provided between the second subcell 320 and the metal oxynitride layer 303 for protection of the first undoped amorphous silicon layer 322 (i.e., the a-Si(i) layer).
[0047] In general, it is understood that the specific configuration of the first and second subcells is not particularly limited, and each of them may have multiple sublayers and one or more intermediate layers disposed between the first and second subcells. Furthermore, it is noted that the monolithically integrated multi-junction photovoltaic device may include three or more subcells, as long as the individual subcells are electrically connected in series between a single pair of terminals. Examples of triple subcell structures include, but are not limited to, a double-sided monolithically integrated multi-junction photovoltaic device having a top subcell (second subcell) having a photoactive region containing a perovskite material, a middle subcell (first subcell) having a silicon heterojunction (SHJ), and a bottom subcell having a photoactive region containing a perovskite material.
[0048] It will also be appreciated by those skilled in the art that although all of the illustrated embodiments of the invention relate to photovoltaic devices with multijunction structures as illustrated, in which the top perovskite sub-cell has a planar heterojunction configuration, with a dense layer of perovskite between layers of p-type and n-type materials without open porosity, the interconnect layers described herein are equally applicable to multijunction photovoltaic devices in which the top perovskite sub-cell has other configurations. For example, the top perovskite sub-cell may have a porous framework of semiconducting or dielectric material on which the perovskite material is provided, either as a thin layer or as a capping layer. As a further example, the top perovskite sub-cell may have only one charge transport region, as it has been shown that photovoltaic devices with photoactive perovskites that operate without hole transport materials can be formed.
[0049] Manufacturing method In a second embodiment, the present invention relates to a method of manufacturing a multi-junction photovoltaic device having a first subcell with a layer comprising a perovskite light absorber material and a second subcell, the method comprising depositing a metal (e.g. titanium) oxynitride layer between the first and second subcells. In a preferred embodiment, the multi-junction photovoltaic device is as described with respect to the first embodiment above.
[0050] More specifically, the method may include providing a bottom subcell (i.e., the second subcell) on a back electrode, depositing a metal (e.g., titanium) oxynitride layer on the bottom subcell, providing a top subcell (i.e., the first subcell) on the metal (e.g., titanium) oxynitride layer having a layer having a perovskite absorber material, and providing a front electrode on the top subcell.
[0051] It is understood that the process of providing the first and second subcells, and the front and back electrodes is not particularly limited and may be appropriately selected by those skilled in the art from various techniques depending on the nature of each of the (sub)layers. Typical techniques include, but are not limited to, solution deposition techniques (e.g., by screen printing, doctor blading, slot dye coating, spin coating, etc.), sol-gel techniques, vapor deposition (e.g., physical vapor deposition (PVD), plasma enhanced chemical vapor deposition (PECVD)), sputter deposition, pulsed laser deposition, vacuum evaporation, electroplating, or the like. However, from the standpoint of simplicity and equipment costs, it may be preferable to avoid PECVD techniques in order to fully exploit the advantages of the present invention.
[0052] In a preferred embodiment of the invention, the metal (e.g. titanium) oxynitride layer is deposited by physical vapor deposition (PVD), preferably by sputter deposition, and most preferably by magnetron sputtering, which does not require complex equipment and allows for rapid deposition with consistent results.
[0053] In a further preferred embodiment, a magnetron sputtering system is used to deposit TiO using a titanium nitride (TiN) target and an Ar / O gas mixture. x N y A TiO layer can be deposited by simply varying the oxygen flow rate. x N y It allows fine tuning of the optical and electrical properties of the thin film. The power, frequency and base pressure of the sputtering are not particularly limited and can be appropriately adjusted by those skilled in the art. x N y An exemplary method for adjusting magnetron sputtering conditions to provide a layer is disclosed in F. Chen et al., Optical Materials Express 2014, 4(9), 1833-1847.
[0054] By using sputtering techniques, deposition rates of the titanium oxynitride layer of 0.4 nm / s or more can be achieved, for example 0.6 nm / s or more or 0.8 nm / s or more, where each value refers to the average thickness of the titanium oxynitride layer, and thus the intermediate layer can be deposited at a rate significantly higher than the specialized PECVD techniques used in the art.
[0055] It will be understood that the preferred features of the first and second embodiments may be freely combined in any combination, except those combinations in which at least some of the features are mutually exclusive.
[0056] Given the above disclosure, many other features, modifications, and improvements will become apparent to one of ordinary skill in the art.
[0057] Working Example The invention is illustrated by the following examples.
[0058] Example 1: The solar-to-electricity power conversion efficiency (PCE) of perovskite / silicon tandem solar cells depends on the refractive index n of the intermediate layer material. IL is between the refractive index of the perovskite material and that of the silicon material (n PVSK <n IL <n Silicon ) can be enhanced by placing an intermediate layer between the two absorber layers. By doing so, such a layer can reduce the reflection of infrared light that occurs at the interface region between the two absorbers. To maximize this beneficial effect, the intermediate layer should have a refractive index (n IL,800 = 2.7) and a thickness of about 100 nm. Thus, the interference effect between the light impinging on the upper and lower interfaces of the intermediate layer is most efficiently exploited. It has been demonstrated that doped nanocrystalline silicon oxide (nc-SiOx) can be used very efficiently as such an intermediate layer, since it can be manufactured with optoelectronic properties exploiting optical effects without degradation of the electrical performance, e.g. due to additional series resistance losses. However, the complex manufacturing method (PECVD) and the relatively slow deposition rate of nc-SiOx motivate the search for alternative materials that can be more easily produced. According to the above mentioned invention, sputtered TiO x N y Perovskite / silicon tandem cells with an intermediate layer have been fabricated. Results currently show that the best films have a refractive index n of ~2.4 at 800 nm wavelength. 800 (TiO x N y The maximum achievable refractive index is n ~2.5. 800 Due to this lower maximum refractive index, a slightly lower optical enhancement is expected compared to the prior art nc-SiOx.
[0059] method A group of silicon heterojunction (SHJ) solar cells fabricated in parallel with a reference group of SHJ solar cells with no intrinsic optical interlayer were coated with a 100 nm thick TiO x N y SHJ cell fabrication and TiO deposition x N y The deposition was performed as described by Chen et al. in “Control of optical properties of TiN x O y The layers were sandwiched between 20 nm thick TCO layers to avoid problems with electrical contacts. The device stack is shown in Figure 7. The additional TCO layer only has a relatively small effect optically due to its small thickness.
[0060] The perovskite top cell was deposited according to the latest method described in Al-Ashouri et al. “Monolithic perovskite / silicon tandem solar cell with >29% efficiency by enhanced hole extraction”, Vol. 370, 6522, 1300-1309, (2020). The tandem cell was then characterized by current-voltage (IV) measurements under illumination with care taken to adequately mimic the AM1.5G standard solar spectrum (representative IV measurements are shown in Figure 8). In addition, external quantum efficiency measurements were performed using bias light to measure each subcell independently. Optical simulations were performed. The optical properties of the films were measured by spectroscopic ellipsometry (examples of extracted refractive index and absorption or extinction coefficient “nk” are shown in Figure 9). Optical simulations were performed using the transfer matrix method. The results of the optical simulations are shown in the Supporting Information (see Figures 10 and 11).
[0061] Results and Discussion Figure 4 shows three from "split without intermediate layer" and "TiOx N y IV characteristics of six tandem cells, including three from the "split": power conversion efficiency (PCE), short circuit current density (J SC ), open circuit voltage (V OC ), and the change (delta) in fill factor (FF). These results have been normalized to the mean value in the “no hidden layer split” for each of these four parameters to show the differences.
[0062] Box plots of each distribution are also shown in Figure 4. PCE is the TiO x N y The splitting is slightly lower on average, the reason for this is the change in the average FF. On the other hand, it can be observed that the average Jsc increases from +0.2 to +0.3 mA / cm 2 The delta Jsc of is +1.8mA / cm 2 A gain of 1.0% can be observed, which is significantly lower than that in another nc-SiOx reference, Mazzarella et al., “Infrared Light Management Using a Nanocrystalline Silicon Oxide Interlayer in Monolithic Perovskite / Silicon Heterojunction Tandem Solar Cells with Efficiency above 25%”, Advanced Energy Materials, Vol. 9, 14, (2019) (compare also Fig. 11). Furthermore, the average Voc increases slightly.
[0063] Figure 5 shows the measured quantum efficiency of two representative cells from each split. It can be seen that interference effects are visible in the EQE of the silicon bottom cell. Such interference effects have been shown to be caused by light reflected at the interface region (Mazzarella et al., Advanced Energy Materials, Vol. 9, Issue 14, April 11, 2019). Furthermore, the EQE of the cell with the intermediate layer shows a reduced amplitude of the interference fringes. Comparing this experimentally observed EQE curve with the simulated EQE (Figure 10), a similar behavior of reduced amplitude of the interference fringes is observed. The positions of the maximum and minimum of the interference fringes are not exactly at the same positions, which is likely due to the slightly different perovskite absorber thickness between the experiment and the simulation.
[0064] Figure 6 shows three cells without an intermediate layer and a TiO x N y For each of the three cells with an intermediate layer, the Jsc values of the perovskite sub-cell and silicon sub-cell calculated from the EQE curves and the AM1.5G standard solar spectrum are shown. The bottom cell is TiO x N y Approximately 0.3 mA / cm from the middle layer 2 It can be seen that we obtain a gain of 100%. This gain is not as high as theoretically predicted (compare Fig. 11). This could be because the refractive index on the cell is somewhat different compared to the one measured on the glass substrate. Alternatively, the additional contact layer, which we omitted from the simulation, could have a larger effect than initially expected.
[0065] Moreover, it can be seen in Fig. 6 that in all cases the Jsc values of the perovskite subcell are larger than those of the silicon subcell. Since the Jsc of the tandem device is limited by the Jsc of the cell with the lower current density (due to the monolithic series connection), the gain in Jsc seen in Fig. 4 can be explained by the increase in Jsc in the limiting subcell. Therefore, it can be inferred that the EQE and IV measurements are in good agreement. What is somewhat surprising is the decrease in Jsc of the perovskite subcell. Since less light is reflected back to the top cell, a small change can be expected based on the simulations. However, the magnitude of this change should be much smaller than the gain in the silicon bottom subcell. Since the variation in the “no interlayer” perovskite subcell Jsc group is the largest among the four Jsc groups, this unexpected large decrease may be caused by something unrelated to the experiment, such as measurement error or process variation in one of the top cell processes. The difference in the top cell EQE around 400 nm wavelength visible in Figure 5, which is not seen in the theoretical prediction (compare Figure 10), supports this hypothesis: light at 400 nm wavelength should not "see" the intermediate layer and should be completely absorbed by the top cell.
[0066] summary In summary, the above results for the tandem cell indicate that TiO x N y The use of an intermediate layer reduces the reflection losses of perovskite / silicon tandem cells, occurring in the infrared region of the spectrum, to 0.3 mA / cm 2 This supports the theoretical prediction that the effect of the ion exchange coefficient can be significantly reduced. [Explanation of symbols]
[0067] 100 / 200 / 300: Monolithic multijunction photovoltaic devices 110 / 210 / 310: 1st subcell 120 / 220 / 320: Second subcell 101 / 201 / 301: Front electrode 102 / 202 / 302: Back electrode 103 / 203 / 303: Metal (e.g. titanium) oxynitride layers 204: Light-transparent conductive oxide layer 205: doped amorphous silicon layer (n-type) 305: doped amorphous silicon layer (p-type) 211: Perovskite layer 212 / 312: n-type semiconductor layer 213 / 313: p-type semiconductor layer 221 / 321: Crystalline silicon layer 222 / 322: First undoped amorphous silicon layer 224 / 324: second undoped amorphous silicon layer 225: doped amorphous silicon layer (p-type) 325: doped amorphous silicon layer (n-type)
Claims
1. 1. A multijunction photovoltaic device having a first subcell and a second subcell, the first subcell having a layer comprising a perovskite light absorber material, and a metal oxynitride layer between the first and second subcells.
2. The multijunction photovoltaic device of claim 1 , wherein the device has a monolithically integrated structure.
3. A multi-junction photovoltaic device as described in claim 2, wherein the device has a tandem structure.
4. The multijunction photovoltaic device of claim 1 , wherein the metal is an early transition metal.
5. A multi-junction photovoltaic device as claimed in any one of claims 1 to 4, wherein the metal is selected from Ti, W, Mo, Hf, Ta, Nb, Zr, Cr, and V.
6. A multi-junction photovoltaic device as described in any one of claims 1 to 5, wherein the metal is Ti.
7. 7. A multijunction photovoltaic device according to any preceding claim, wherein the first sub-cell also comprises an n-type semiconductor layer and a p-type semiconductor layer on either side of the layer comprising the perovskite light absorber material.
8. 8. The multijunction photovoltaic device of claim 7, wherein the metal oxynitride layer is adjacent to and in contact with either the n-type semiconductor layer or the p-type semiconductor layer.
9. 8. The multijunction photovoltaic device of claim 7, wherein one of the n-type semiconductor layer or the p-type semiconductor layer is adjacent to and in contact with a major surface of an optically transparent conductive oxide layer, and an opposite major surface of the optically transparent conductive oxide layer is adjacent to and in contact with the metal oxynitride layer.
10. 10. The multijunction photovoltaic device of claim 1, wherein the second subcell comprises a layer of crystalline silicon light absorber material.
11. The multijunction photovoltaic device of claim 10 , wherein the second subcell comprises a heterojunction photovoltaic device.
12. 12. The multijunction photovoltaic device of claim 11, wherein the second subcell has a layer of crystalline silicon sandwiched between two layers of undoped amorphous silicon.
13. 13. The multijunction photovoltaic device of claim 12, wherein a layer having doped amorphous silicon is provided between the layer of undoped amorphous silicon and the metal oxynitride layer.
14. The multijunction photovoltaic device of claim 12, wherein the metal oxynitride layer is a titanium oxynitride layer, and a layer having doped nanocrystalline silicon oxide is provided between the layer of undoped amorphous silicon and the titanium oxynitride layer.
15. In the following order: a) front electrode; b) a first subcell having a layer with a perovskite light absorber, the first subcell having an n-type semiconductor layer on one surface of the layer with a perovskite light absorber and a p-type semiconductor layer on the other surface of the layer with a perovskite light absorber; c) the metal oxynitride layer; d) a doped amorphous silicon layer; e) a second subcell having a layer of crystalline silicon absorber material between the first and second undoped amorphous silicon layers; and f) back electrode; 10. The multijunction photovoltaic device of claim 1 comprising:
16. The multi-junction photovoltaic device of claim 15, further comprising a light-transmitting conductive oxide layer between layers b) and c).
17. the p-type semiconductor layer of the first subcell is adjacent to the metal oxynitride layer; the doped amorphous silicon layer is an n-type amorphous silicon layer; the second subcell further comprising a p-type amorphous silicon layer adjacent to the back electrode. The multijunction photovoltaic device of claim 15.
18. The p-type semiconductor layer of the first subcell is adjacent to the optically transparent conductive oxide layer; the doped amorphous silicon layer is an n-type amorphous silicon layer; the second subcell further comprising a p-type amorphous silicon layer adjacent to the back electrode. The multijunction photovoltaic device of claim 16.
19. A multi-junction photovoltaic device as described in any one of claims 1 to 18, wherein the metal oxynitride layer is adapted to have a refractive index between 2.3 and 3.
7.
20. A multi-junction photovoltaic device as described in claim 19, wherein the metal oxynitride layer is adapted to have a refractive index between 2.3 and 2.
9.
21. 21. The multijunction photovoltaic device of claim 1, wherein the metal oxynitride layer has a thickness between 20 nm and 200 nm.
22. 1. A method of manufacturing a multi-junction photovoltaic device having a first subcell having a layer having a perovskite light absorber material and a second subcell, the method comprising depositing a metal oxynitride layer between the first subcell and the second subcell.
23. 23. The method of manufacturing a multi-junction photovoltaic device of claim 22, wherein the metal oxynitride layer is deposited by physical vapor deposition and / or the deposition rate of the metal oxynitride layer is 0.4 nm / s or greater.
24. A method for manufacturing a multijunction photovoltaic device as described in claim 23, wherein the metal oxynitride layer is titanium oxynitride.
25. A method for manufacturing a multi-junction photovoltaic device as described in claim 23 or 24, wherein the metal oxynitride layer is deposited by sputter deposition.
Citation Information
Patent Citations
Laminated photovoltaic device and production method thereof
CN113451434A
Tandem solar cell, tandem solar cell module including the same, and manufacturing method thereof
JP2018011058A
Multijunction Photovoltaic Devices
JP2020508570A
Multijunction photovoltaic device
WO2018150203A1
Multi-junction photovoltaic device
WO2019048839A1